La Belgique face aux investissements étrangers : une approche sociologique. - Beckers, Marc; Frère, Jean-Pol; Saucier, Roger; Torrisi, Giuseppe P. (Leuven : Université de Louvain, 1973)
Bibliotheek François Vercammen
Frans
Monografie